2011
DOI: 10.1038/ki.2011.40
|View full text |Cite
|
Sign up to set email alerts
|

Continuous cognitive improvement 1 year following successful kidney transplant

Abstract: Successful kidney transplantation was recently shown to lead to improvement in the cognitive performance of patients on chronic dialysis. To examine whether the early cognitive benefits of transplantation continue to develop over time, along with the patients' ongoing recovery, we addressed these questions in a prospective controlled study of 27 dialyzed patients who subsequently received a kidney transplant, 18 dialyzed patients awaiting kidney transplant, and 30 matched controls without kidney disease. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 47 publications
5
71
4
4
Order By: Relevance
“…The default mode network and the sensorimotor network remained statistically different from controls even 6 months after kidney transplantation. These findings provide neural substrates for different brain cognition function recovery patterns in accordance with previously reported results (8,11). Different networks are responsible for distinct domains of brain function.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The default mode network and the sensorimotor network remained statistically different from controls even 6 months after kidney transplantation. These findings provide neural substrates for different brain cognition function recovery patterns in accordance with previously reported results (8,11). Different networks are responsible for distinct domains of brain function.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies showed that some domains of cognition function, especially memory, did not fully return to normal until 1 year after successful kidney transplantation (8). The default mode network is involved in numerous brain functions, including memory, visual and Figure 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful transplantation, which can restore solute clearances to more than half normal, improves overall quality of life and enhances specific functions, including sleep, cognition, exercise capacity, and growth in children. [5][6][7][8][9] …”
mentioning
confidence: 99%